Allaying pediatric preoperative anxiety, where are we now? - A nationwide survey - Shreya Bharat Shah; Renu Sinha; Sana Yasmin Hussain; Amit Kumar; Anju Gupta (Wolters Kluwer Medknow Publications, 2023)
Background: Preoperative anxiety (PA) in children is a common phenomenon associated with various negative patient outcomes. Allaying PA is accepted as a standard of care, but its use is not universal and often overlooked. This survey is designed to evaluate the nationwide current practice patterns and attitudes of anesthesiologists toward the practice of allaying PA in children. Materials and Methods: A questionnaire of 25 questions, including information on methods of relieving PA in children, reasons for noncompliance, and associated complications, was framed. It was circulated among members of the Indian Society of Anaesthesiologists through an online survey of Google Forms and manually. Results: Four hundred and fifty anesthesiologists were surveyed. Responses were predominantly from anesthesiologists practicing in medical colleges across the country. Although 97% of the surveyed respondents practiced anxiety-relieving strategies, only 37% used it consistently. Seventy-three percent of anesthesiologists practiced both pharmacological and nonpharmacological techniques. The most common reason for avoiding premedication was an anticipated difficult airway (88%). Inadequate sedation was a commonly reported problem. Ninety-five percent of participants felt that PA-relieving strategies should be integral to pediatric anesthesia practice. The most common reason for not following these practices was an inadequate hospital infrastructure (67%). Ninety-seven percent of the participants believed that more awareness is required on this crucial perioperative issue. Conclusion: Only 37% of the surveyed anesthesiologists consistently used some form of PA-relieving strategy and the practice varied widely. Further improvement and team approach involving anesthesiologists, surgeons, and nurses is required to ensure the quality of pediatric PA-relieving services and establish it as a standard of care.